Chinese university students' attitude towards self and others in reflective journals of intercultural encounter. (August 2019) - Chen, Yanqing; Zheng, Xuan
Abstract: Journal writing involving guided reflections on intercultural experiences has a potential in facilitating intercultural communicative competence (ICC). However, most of the research on reflective journal writing relied on content-based thematic analysis alone and neglected the use of language that reveals, complements or even distorts the true meaning of the content. Using linguistic tools provided by appraisal theory, the study investigated the attitudinal changes towards self and others in the reflective journals of intercultural encounter written by 41 undergraduates in an College English Intercultural Communication class in a Chinese university. Positive attitudinal changes were found, including the extension of reflection from people in the incidents to cultures they represented, more appreciation of the intercultural experience, more objectivity and empathy for others, and critical reflection on one's own behaviour in intercultural experience and one's initial ethnocentric interpretation of it. Problematic tendencies included outgroup-favouritism, non-judgement on the surface and overgeneralisation. Suggestions were provided for teachers who intend to use reflective journals in facilitating students' ICC growth.